Photochemical Reductive C–C Coupling with a Guanidine Electron Donor. Issue 29 (27th September 2016) - Wiesner, Sven; Walter, Petra; Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract : The metal‐free photoinduced reductive C–C coupling reactions of a number of substituted benzyl halides (15 examples) with the organic electron‐donor 2, 3, 5, 6‐tetrakis(tetramethylguanidino)pyridine are evaluated. Depending on the substituents at the benzyl group, a C–C coupling product yield in the range 50–95 % is achieved. The photochemical benzyl‐radical formation by homolytic N–C bond cleavage of the initially formed benzyl‐pyridinium salts is the rate‐determining step of these reactions. Electron‐withdrawing as well as ‐donating substituents at the phenyl group increase the reaction rate. Quantum chemical computations did not reveal any correlation between either the enthalpy or Gibbs free energy of the N–C bond cleavage step and the experimentally determined first‐order rate constants. Instead, the structural difference between the excited state generated by irradiation and the electronic ground state of the pyridinium ions could be used to rationalize the differences in the reaction rates. Abstract : The yields and rate constants for the photochemical reductive C–C coupling of a number of benzyl halides with the electron‐donor 2, 3, 5, 6‐tetrakis(tetramethylguanidino)pyridine are studied. The results for benzyl halides with electron‐withdrawing and ‐donating substituents and quantum‐chemical calculations are used for a detailed analysis of the mechanism of metal‐free C–C coupling.